IBN ‘ARABĪ’S CREATIVE IMAGINATION AND ITS ECHOES IN D.H. LAWRENCE’S WOMEN IN LOVE - Kortas, Cyrine (Sekolah Tinggi Agama Islam Sadra, 2024)
This paper employs textual analysis and comparative literary methods to examine the mystical and spiritual dimensions of D. H. Lawrence's Women in Love through the lens of sufi mysticism. It posits that Lawrence's engagement with sufi philosophy and literature significantly informed his portrayal of love as a transformative spiritual journey. By scrutinizing Lawrence's use of symbolism, imagery, and character development, particularly in the character of Birkin, the study aims to demonstrate how the novel reflects a profound resonance with sufi concepts, such as the unity of the universe and the mystical path for knowledge. This comparative approach seeks to illuminate how Women in Love can be interpreted as a modernist exploration of spiritual fulfillment within a context of societal disintegration, thereby establishing its place within Lawrence's broader “New Man” fiction. Through Birkin, Lawrence explores the complexities of the human psyche and the potential for transcendence through a passionate, yet spiritually grounded love. The paper’s comparative approach seeks to illuminate how the novel contributes to Lawrence's broader “New Man” fiction, a visionary archetype striving for a harmonious integration of body, mind, and spirit. Lawrence’s “New Man” embodies a radical departure from traditional masculinity that collapsed after the war. The new archetype Lawrence envisions in the light of a sufi reading is not the product of societal expectations but an individual attempt at authenticity.